P262 Cognitive outcomes of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) and electroconvulsive therapy (ECT) in the treatment of major depression: A systematic review and meta-analysis. Issue 3 (March 2017) - Kedzior, K.K.; Schuchinsky, M.; Gerkensmeier, I.; Loo, C.
Abstract : Background: Compared to high-frequency repetitive transcranial magnetic stimulation (HF-rTMS), electroconvulsive therapy (ECT) appears to be particularly effective in the treatment of unipolar psychotic major depression. The aim of the current study was to compare the short-term cognitive effects of the two methods in the treatment of major depression using a systematic literature review and a meta-analysis. Methods: A systematic literature search of PubMed, PsycInfo, and Medline (any time – 16.02.2016) identified k  = 118 studies. Of those k  = 5 met the inclusion criteria (parallel design, rTMS with >1 Hz frequency, diagnosis of major depression). Cognitive functioning was measured as overall cognitive impairment, working memory, anterograde memory (learning), and retrograde memory (free-recall) using several standardised scales administered at baseline and at the end of the short-term stimulation phase. The effect sizes (standardised mean difference, Hedges' g ) were pooled according to random-effects meta-analysis with inverse-variance weights. Results: The studies utilised a single-blind design ( k  = 1) or open-label designs ( k  = 4). Mixed samples with psychotic depression were included in two studies. All k  = 5 studies utilised 10–20 sessions of 10-Hz rTMS of the left dorsolateral prefrontal cortex. Most studies applied ECT as a right unilateral stimulation with 2.5 times the seizure threshold energy in 2–14 sessions. HF-rTMS was applied as an augmentation therapy in three studies and ECT was applied as an augmentation therapy in four studies. The pooled weighted effects (from three studies each) showed that the overall cognitive impairment and working, anterograde, and retrograde memory tended to improve after the short-term treatment compared to baseline. However, the magnitude of these effects did not differ between ECT vs. HF-rTMS. On the individual study level, anterograde and retrograde memory were impaired after ECT but not HF-rTMS in one study with severely depressed unipolar non-psychotic patients. Conclusion: Short-term ECT and HF-rTMS treatments appear to have similar effects on cognitive functioning in unipolar major depression. However, cognitive outcomes need to be assessed in further blinded randomised trials with homogeneous samples and beyond the short-term treatment phases.